Contribution to turbulence suppression of the radial wavenumber spectral shift induced by negative bias in the J-TEXT tokamak - Daiqing Xu; Hai Liu; Junren Shao; Yuhong Xu; Zhipeng Chen; Jun Cheng; Haifeng Liu; Xianqu Wang; Jie Huang; Xin Zhang; Changjian Tang; Zhongyong Chen; et al. (Nuclear Fusion)
The effects of negative bias on the turbulence and particle transport in edge plasma of J-TEXT tokamak are addressed in this work. An obvious decline in the turbulent particle transport is observed when the bias voltage reaches −200 V. The suppression time of turbulence intensity after the bias turned on is very short (<200 μ s), much less than the reconstruction time of equilibrium electric field E _r (several milliseconds), which signifies that the turbulence suppression cannot be attributed to the decorrelation effect of mean E _r × B shear flow. Analysis of the radial wavenumber ( k _r ) spectrum of the floating potentials at the edge plasma shows that when increasing the bias voltage, the amplitude of wavenumber spectrum decreases monotonously. Whereas, only when the bias voltage reaches a threshold (−200 V), the k _r corresponding to the peak of the spectrum (i.e. k _r,peak ) shifts toward more negative values, followed by the suppressions of turbulence intensity and particle transport. Meanwhile, the Reynolds stress is found to be reduced and the tilt of turbulent eddy structures is verified in this experiments. The results are in agreement with the spectral shift model (Staebler et al 2013 Phys. Rev. Lett. 110 055003), which indicates the turbulence suppression in short time is due to scattering turbulence energy to the high k _r region where the energy is easy to dissipate.